Energy harvesting from a convection-driven Rijke-Zhao thermoacoustic engine - Zhao, Dan (2014)
A convection-driven Rijke-Zhao thermoacoustic engine is developed. It can produce intensive oscillations at two different temperatures. Furthermore, it does not involve any heat exchanger and stack/regenerator, which play critical roles in conduction-driven standing- or travelling-wave engines. Thus, the Rijke-Zhao engine is much simpler in design and lower cost in fabrication. To demonstrate its potential of energy-harvesting, a design for the conversion of heat into electricity via sound is proposed by integrating Rijke-Zhao engine with a piezoelectricgenerator. The preliminary experimental results are presented. And it is found that 60% more power is generated than that from conduction-driven standing-wave thermoacoustic-piezoelectric resonator [Smoker et al., J. Appl. Phys. 111, 104901, (2012)]. In order to gain insights on the generation mechanism of the thermoacoustic oscillations in the present energy-harvesting system, 2D numerical simulations are conducted. Comparing the numerical results with the experimental one reveals that good quantitative agreement is obtained.